Licochalcone A selectively modulates mTORC1‐TFEB to enhance autophagy and demonstrates neuroprotective effects in a mouse model of Parkinson's disease - Sisi Wang; Ziyang Ding; Zhou Zhu; Xiaoru Zhong; Ashok Iyaswamy; Yaping Niu; Wei Zhang; Jichao Sun; Yulin Feng; Chuanbin Yang; Jigang Wang (Brain-X, 2025)
Abstract Activation of transcription factor EB (TFEB), a key regulator of autophagy induction and lysosomal biogenesis, is considered a promising therapeutic strategy for treating the currently incurable Parkinson's disease (PD). However, most TFEB activators also inhibit mTORC1, which regulates several other cellular pathways. Therefore, small molecules that selectively modulate the mTORC1‐TFEB pathway represent a novel and promising approach for treating PD. This study reveals that licochalcone A (LA), a flavonoid derived from the widely used Chinese herbal medicine licorice, selectively activates TFEB‐mediated autophagy and exerts neuroprotective effects in a mouse model of PD. Specifically, we found that LA promoted the displacement of TFEB to the nucleus and enhanced autophagic flux. Knockout of the TFEB gene effectively inhibited LA‐induced autophagy, suggesting that LA induced autophagy through TFEB activation. Mechanistic investigations revealed that LA activates TFEB through the Rag C‐mediated non‐canonical mTORC1 pathway, rather than through the canonical mTOR signaling or the PPP3/calcineurin pathway. Moreover, in a mouse model of MPTP‐induced PD, oral administration of LA reduced the depletion of dopaminergic cells in the striatum and substantia nigra and alleviated motor symptoms. In conclusion, LA selectively modulates the mTORC1‐TFEB pathway to induce autophagy, and reduces dopaminergic neuron loss and alleviates motor dysfunction in a mouse model of PD. These findings suggest that LA could serve as a novel TFEB activator and a potential therapeutic agent for treating PD.